Using an App to monitor postoperative pain at home in pediatric patients. (June 2021) - Tiozzo, Emanuela; Biagioli, Valentina; Brancaccio, Matilde; Ricci, Riccardo; Marchetti, Anna; Dall'Oglio, Immacolata; Gawronski, Orsola; Bonanni, Fabiana; Piga, Simone; Celesti, Lucia; Offidani, Caterina; Tozzi, Alberto Eugenio; et al.
A prospective comparative study was conducted in 487 pediatric patients (69% male, mean age = 6.4 ± 4.0) to evaluate (a) the incidence, intensity, and characteristics of pain in pediatric patients at home during the first 24 hours and 5 days after surgery and (b) the factors associated with higher pain intensity, including the impact of an application (App) compared to the paper-and-pencil approach. Postoperative pain was assessed by patients or their parents at home using the 'Bambino Gesù' Children's Hospital (Ospedale Pediatrico Bambino Gesù, OPBG) tool for participants aged 4–17 years or the Faces, Legs, Arms, Cry, and Consolability scale for participants less than four years old. Participants were assigned to two groups: those who used the paper-and-pencil version of the pain scale and those who used the App. Overall, 209 of the 472 (44%) participants reported pain during the first 24 hours, and 92 of the 420 (22%) reported pain between one and five days after surgery. Higher pain intensity scores were associated with being in the App group, directly assessing own pain, and using the OPBG tool. The App was effective in facilitating pain assessment. Health professionals could empower pediatric patients and their parents in assessing pain at home through a dedicated App.